Growth performance and gut health of Escherichia coli–challenged weaned pigs fed canola meal-containing diet. (22nd June 2021) - Hong, Jinsu; Ariyibi, Samuel; Antony, Linto; Scaria, Joy; Dilberger-Lawson, Steven; Francis, David; Woyengo, Tofuko Awori
Abstract: An experiment was conducted to evaluate the effects of including canola meal (CM ) in diets for weaning pigs challenged with a F18 strain of Escherichia coli on growth performance and gut health. A total of 36 individually housed weaned pigs (initial body weight [BW ] = 6.22 kg) were randomly allotted to one of the three diets (12 pigs/diet). The three diets were corn–soybean meal (SBM )-based basal diet (control diet) and the basal diet with 0.3% zinc oxide, 0.2% chlortetracycline, and 0.2% tiamulin (antibiotic diet) or with 20% CM diet. The diets were fed in two phases: Phase 1: days 0 to 7 and Phase 2: days 7 to 20. All pigs were given an oral dose of 2 × 10 9 CFU of F18 strain of E. coli on day 7. Fecal score was assessed daily throughout the trial. Dietary antibiotics increased ( P < 0.05) overall average daily gain (ADG ) and average daily feed intake (ADFI ) compared by 48% and 47%, respectively. Dietary CM increased ( P < 0.05) overall ADG and ADFI by 22% and 23%, respectively; but the ADG and ADFI values for CM-containing diet did not reach those for the antibiotics-containing diet. Dietary antibiotics reduced ( P < 0.05) fecal score; however, dietary CM unaffected fecal score. Dietary antibiotics decreased ( P < 0.05) liver weight per unit live BW by 16% at day 20, whereas dietary CM did not affect liver weight per unit live BW (29.2 vs. 28.6). Also, dietary antibiotics increased ( P < 0.05) serum triiodothyronine and tetraiodothyronine levels for day 14, whereas dietary CM did not affect the serum level of these hormones. Dietary antibiotics reduced ( P < 0.05) the number white blood cells and neutrophils by 38% and 43% at day 20, respectively, whereas dietary CM tended to reduce ( P = 0.09) the number white blood cells by 19% at day 20. The number white blood cells for CM diet tended to be greater ( P < 0.10) than that for antibiotics diet. The dietary antibiotics decreased ( P < 0.05) the concentration of individual volatile fatty acids and hence of total volatile fatty acid in cecum by 61% at day 20, whereas dietary CM decreased ( P < 0.05) cecal butyric acid concentration by 61% and tended to reduce ( P < 0.10) total volatile fatty acid concentration by 30% at day 20. In conclusion, the dietary inclusion of 20% CM improved ADG and tended to reduce white blood cell counts. Thus, inclusion of CM in antibiotics-free corn-SBM-based diets for weaned pigs that are challenged with F18 strain of E. coli can result in their improved performance partly through a reduction of the inflammatory response.